From tweets to markets: Lebanon’s policy uncertainty and volatility spillovers in MENA stock markets - Sumru, Altug (2025)
This paper examines the spillover effects of policy uncertainty in Lebanon on stock market volatility in seven MENA countries using a network connectedness approach. For this purpose, it constructs an economic policy uncertainty index for Lebanon using data extracted from Twitter (now X) for the period January 1, 2011, to January 18, 2023. The Twitter-based Economic Policy Uncertainty Index (TEPU) acts as the most important network node for transmitting the policy uncertainty that occurred in Lebanon during various episodes within the sample period. The stock markets of Kuwait and Qatar, on the one hand, and those of Egypt and Jordan, on the other, are the largest net recipients of this policy uncertainty during such episodes. The TEPU for Lebanon, together with the Saudi Arabian stock market, plays an important role in terms of shock propagation during 2017–2018, when political tensions with Saudi Arabia spiraled. However, on average, the Saudi Arabian and United Arab Emirates stock markets account for the largest fraction of the shock propagation values, attesting to their importance in the MENA financial markets.